Prevalence of neurofascin-155 antibodies in patients with multiple sclerosis - Stich, Oliver; Jarius, Sven; Wildemann, Brigitte (Journal of the neurological sciences, 2016)
Introduction - Antibodies against neurofascin, an axo-glial protein located around the node of Ranvier, have been shown to contribute to axonal pathology both in vitro and in experimental autoimmune encephalomyelitis models. Moreover, small case studies have reported anti-NF antibodies in samples from patients with progressive multiple sclerosis (MS). - Patients and methods - Building up on this observation, we compared the anti-NF reactivity in serum samples from 83 chronic progressive MS (PMS) patients to those with relapsing remitting MS (RRMS, n=159) and 50 healthy controls. Anti-NF seroreactivity was quantified by enzyme-linked immunosorbent assay using recombinant rat neurofascin. In addition, to identify a potential intrathecal anti-NF antibody synthesis, we calculated the specific antibody index in paired cerebrospinal fluid and serum samples from MS patients with positive anti-NF seroreactivity. - Results - Prevalence of anti-NF seroreactivity in PMS patients (4.8%; all with primary progressive MS) was significantly higher than that detected in RRMS (0.6%; p=0.030). However, we found no significant difference between PMS patients and healthy controls (2.0%; p=0.408). MS patients with positive anti-NF reactivity experienced an above-average progression of disability compared to MS natural-history controls. Anti-NF-specific intrathecal antibody synthesis was not detected in MS patients with positive anti-NF seroreactivity. - Conclusions - Although present only in a minor subgroup, seroprevalence of anti-NF reactivity was significantly more frequent in patients with PMS than in those with RRMS, but was also occasionally found in healthy controls. Further prospective studies are warranted to investigate whether anti-NF antibodies anticipate disease progression.